'It's definitely part of who I am in the role'. Developing teachers' research engagement through a subject-specific Master's programme. Issue 1 (1st January 2020) - Woore, Robert; Mutton, Trevor; Molway, Laura
ABSTRACT: In 2014, the final report of the British Educational Research Association and Royal Society for the Arts Inquiry called for teachers to engage both with and in research as a core part of their professional role. After considering some of the reasoning and evidence underpinning this ambition, the authors explore one way in which it might be realised: namely, through a Master's course in teachers' professional learning with a strong component of practitioner research. To do so, they present three case studies of Modern Foreign Languages teachers who have recently completed such a course, investigating the participants' perceptions of both (a) the benefits and drawbacks of the course in terms of their professional learning, and (b) any facilitators and barriers they encountered when completing it. The findings support existing evidence for the positive impact of research engagement on teachers' perceptions of their competence and efficacy. They conclude with a series of personal characteristics that seem likely to support individual teachers' engagement with and in research, and by offering some recommendations for schools, university-based teacher educators and policymakers in terms of how such engagement might be effectively supported.